Republic of Mozambique : Poverty Reduction Strategy Paper; Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2009)
This Joint Staff Advisory Note presents key findings of the Poverty Reduction Strategy Paper Annual Progress Report for the Republic of Mozambique. The government of Mozambique is committed to its medium-term fiscal strategy to make room for private sector credit by avoiding recourse to domestic financing. The government has made large domestic debt repayments since 2002. The IMF staff welcomes the broad coverage of macroeconomic developments in 2007 and the assessment of performance against targets laid out in the government's Economic and Social Plan for 2007.